2009
DOI: 10.1111/j.1751-7133.2008.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Midodrine in Patients With Advanced Heart Failure

Abstract: In many patients, the treatment of heart failure (HF) cannot be optimized because of pre‐existing or treatment‐induced hypotension. Midodrine, a peripheral α1‐adrenergic agonist may allow for up‐titration of neurohormonal antagonist therapy leading to improved outcomes. Ten consecutive patients with HF due to systolic dysfunction and symptomatic hypotension interfering with optimal medical therapy were started on midodrine. After a 6‐month follow‐up, a higher percentage of patients were on optimal HF therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…Similarly, inhalation of the a 1 -AR agonist methoxamine improves exercise performance in patients with significant left ventricular contractile dysfunction (Cabanes et al, 1992). Furthermore, in a small cohort of patients with hypotension due to end stage heart failure, the use of the a 1 -AR agonist midodrine is associated with increased contractile function (Zakir et al, 2009). The authors attributed the benefit to a modest increase in blood pressure that resulted from activation of vascular a 1 -ARs, permitting up-titration of recommended heart failure medications (Zakir et al, 2009).…”
Section: A 1 -Adrenergic Receptors Augment Contractile Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, inhalation of the a 1 -AR agonist methoxamine improves exercise performance in patients with significant left ventricular contractile dysfunction (Cabanes et al, 1992). Furthermore, in a small cohort of patients with hypotension due to end stage heart failure, the use of the a 1 -AR agonist midodrine is associated with increased contractile function (Zakir et al, 2009). The authors attributed the benefit to a modest increase in blood pressure that resulted from activation of vascular a 1 -ARs, permitting up-titration of recommended heart failure medications (Zakir et al, 2009).…”
Section: A 1 -Adrenergic Receptors Augment Contractile Functionmentioning
confidence: 99%
“…Furthermore, in a small cohort of patients with hypotension due to end stage heart failure, the use of the a 1 -AR agonist midodrine is associated with increased contractile function (Zakir et al, 2009). The authors attributed the benefit to a modest increase in blood pressure that resulted from activation of vascular a 1 -ARs, permitting up-titration of recommended heart failure medications (Zakir et al, 2009). However, it is possible that direct activation of cardiac a 1 -ARs contributed to this beneficial effect.…”
Section: A 1 -Adrenergic Receptors Augment Contractile Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate observational study, Zakir and colleagues showed that in ten patients with systolic heart failure and symptomatic hypotension interfering with optimizing medical therapy, the use of Midodrine was associated with a significant increase in the percentage of patients on optimal medical therapy. 13 At the end of the study 57.5% of patients were on optimal dose of ACEI/ARB vs 20% initially, 75% compared to 37.5% of patients were on optimal dose beta blocker, and 95% compared to 43.7% of patients were on optimal Spironolactone/Eplerenone therapy. (Figure 1) The use of Midodrine was further associated with an improvement in left ventricular ejection fraction.…”
Section: Results and Discussion Midodrinementioning
confidence: 99%
“…[18][19][20][21][22] Pyridostigmine is a reversible acetylcholine esterase inhibitor, it augments the effect of the parasympathetic system. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] It is currently used in the treatment of myasthenia gravis. 23 Several efforts to study the effect of Pyridostigmine in animal models of heart failure have been made.…”
Section: Pyridostigminementioning
confidence: 99%